HATI DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Muhammad Nasikin; Iskandar (CV. Adiba Aisha Amira, 2021)
The existence of the heart described by the heart in Islamic scientific discourses quoted from Islamic sources, namely the Al-Quran and Al-Hadith can provide correct understanding and caution for the community in using and maintaining the heart in humans. The study of this research is literature, where the author concludes that a safe heart is a heart that is clean from the filling of other gods besides Allah with lots of istighfar, so that there is no defilement of the heart because of greed that is born to glorify Allah's creation, and to deify it. The heart is always filled by a servant by remembering and establishing love with Allah SWT, including praying, so that the relationship strengthens his belief and develops into the fabric of love among His creatures.